The Role of Cloud Computing in Developing the Accounting Profession in Light of Digital Transformation: A Field Study from the Perspective of Faculty Members in the Accounting Departments at the Universities of Sabratha and Zawiya (Al-Farooq Journal of Sciences, 2026)
This study aimed to investigate the role of cloud computing in developing the accounting profession in the era of digital transformation from the perspective of faculty members in the Accounting Departments at the Universities of Sabratha and Al-Zawiya. The study adopted the descriptive-analytical approach and used a questionnaire as the primary data collection instrument. The study population consisted of 60 faculty members. A total of 55 questionnaires were distributed, 50 were returned, and after excluding 4 invalid responses, 46 valid questionnaires were used for statistical analysis.    The findings revealed a high level of awareness among respondents regarding the importance of cloud computing. The results also indicated a high level of agreement concerning the role of cloud computing in enhancing accountants’ professional competencies and supporting the digital transformation of accounting practices. Furthermore, the simple linear regression analysis confirmed that cloud computing has a positive and statistically significant role in developing accountants’ professional competencies and enhancing the digital transformation of accounting practices. The results also demonstrated a significant positive effect of cloud computing on the overall development of the accounting profession in the context of digital transformation.    The study recommends expanding the adoption of cloud computing applications in educational and professional institutions, updating academic and training programs to meet the requirements of digital transformation, and providing the necessary technological infrastructure to support the effective implementation of cloud computing within the accounting environment.
Keywords: Cloud Computing, Accounting Profession, Digital Transformation, Professional Competencies of Accountants, Digital Accounting Practices